The Effect of Farmers Characteristics on the Productivity of Chili Farming in Moolo Village, Batukara Sub District, Muna District - Hasriati, Hasriati; Hamzah, Awaluddin; Salahuddin, Salahuddin (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
This research was conducted in Moolo Village, Batukara Sub District, Muna District. This study aimed to determine the effect of farmer characteristics on the productivity of chili in Moolo Village, Batukara Sub District, Muna District. This research was conducted from February to July 2020. The population in this study was 28 farmers. Sampling in this study uses the census method, where the researcher takes the entire population of chili farmers in Moolo Village. The analysis used in this study is to use multiple linear regression analysis. Based on the multiple linear regression analysis results, it is known that the variables of land area, production, and labor have a significant effect on the agricultural productivity of chili.